Development of new promising antimetabolite, DFP-11207 with self-controlled toxicity in rodents - Fukushima M; Iizuka K; Jin C; Zhang C; Hong M; Eshima K (Drug Design, Development and Therapy, 2017)
Masakazu Fukushima, Kenzo Iizuka, Cheng Jin, Chun Zhang, Mei Hong, Kiyoshi Eshima Division of Oncology Research and Development, Delta-Fly Pharma Inc., Kawauchi-cho, Tokushima, Japan Abstract: To reduce 5-fluorouracil (5-FU)-induced serious toxicities without loss of antitumor activity, we have developed DFP-11207, a novel fluoropyrimidine, which consists of 1-ethoxymethyl-5-fluorouracil (EM-FU; a precursor form of 5-FU), 5-chloro-2,4-dihydroxypyridine (CDHP; an inhibitor of 5-FU degradation), and citrazinic acid (CTA; an inhibitor of 5-FU phosphorylation). In vitro studies of DFP-11207 indicated that it strongly inhibited the degradation of 5-FU by dihydropyrimidine dehydrogenase (DPD) in homogenates of the rat liver, and also inhibited the phosphorylation of 5-FU by orotate phosphoribosyltransferase (OPRT) in tumor tissues in a similar magnitude of potency by CDHP and CTA, respectively. Especially, DFP-11207 inhibited the intracellular phosphorylation of 5-FU in tumor cells in a dose-dependent manner whereas CTA alone did not protect intracellular 5-FU phosphorylation. These results postulate that DFP-11207 rapidly entered into the cell and the free CTA produced from DFP-11207 inhibited the phosphorylation of 5-FU in the cell. Furthermore, following oral administration of DFP-11207, CTA was found to be highly retained in the gastrointestinal (GI) tract compared to other tissues in rats. Interestingly, EM-FU, the prodrug of 5-FU was found to specifically produce 5-FU by various species of liver microsomes. When DFP-11207 was administered to rats, the plasma level of 5-FU was persisted for a long-time with lower Cmax and longer half-life than that from other 5-FU prodrugs. The antitumor activity of DFP-11207 was evaluated in human tumor xenografts in nude rats and found that DFP-11207 showed an antitumor activity in a dose-dependent fashion and its efficacy is equivalent to reference 5-FU drugs. In striking contrast, DFP-11207 manifested no or less 5-FU-related toxicities, such as a decrease in body weights, GI injury, and myelosuppression, especially thrombocytopenia. Taken together, the preclinical evaluation of DFP-11207 strongly indicates that DFP-11207 be a potential new version of the oral fluoropyrimidine prodrug for further clinical development. Keywords: antimetabolite, 5-FU, citrazinic acid, 5-chloro-2,4-dihydroxypyridine, antitumor activity, myelo-toxicity